English for writing research papers - Wallwork, Adrian. (Springer, 2016)
With easy-to-follow rules and tips, and examples taken from published and unpublished papers, you will learn how to: prepare and structure a manuscript increase readability and reduce the number of mistakes you make in English by writing concisely, with no redundancy and no imbiguity write a title and an abstract that will attract attention and be read decide what to include in the various parts of the paper (Introduction, Methodology, Discussion etc) highlight your claims and contribution avoid plagiarism discuss the limitations of your research choose the correct tenses and style satisfy the requirements of editors and reviewers This new edition contains over 40% new material, including two new chapters, stimulating factoids, and discussion points both for self-study and in-class use.